Nanoscience and nanoengineering advances and applications (CRC Press, 2014)
"Preface The scientific prefix "nano" means one billionth. Therefore, a nanometer is one billionth of a meter, a nanosecond is one billionth of a second and so on. Clusters of atoms and molecules have dimensions in the order a a few nanometers. For example, the diameter of a carbon nanotube is approximately two nanometers and a typical DNA molecule is a little over two nanometers wide. Nanotechnology is often defined as the scientific and engineering know-how to control the arrangement of atoms and molecules enabling novel applications with customized properties. Most formal definitions of nanotechnology usually cites a size upper bound of one hundred nanometers (100 nm). Particles, features, structures, devices, etc., that have dimensions less than 100 nm are referred to as "nano", but in many technologies, this "cutoff" is arbitrary and it is often useful to view structures larger than 100 nm as nanotechnology as well. In order to provide perspective to the reader, it is good to think of the dimensions that nanotechnologists work with compared to objects in the macroscopic world. The two comparisons that I often use to explain relative sizes are that 100 nm is roughly 1000 times smaller than the diameter of a human hair. I also explain that approximately one million carbon nanotubes could be lined up side to side across the diameter of the head of a pin. People have used nanotechnology for hundreds of years but it is only in the last fifty years or so that the drive for miniaturization and the ability to manipulate nanoscale particles, fibers, films and structures has created a technology revolution. Early use of nanoparticles can be seen in the stained glass windows of gothic cathedrals, dichroic glass and in photography"..